READING PSALM 78 MULTIDIMENSIONALLY: THE DIMENSION OF THE READER - Kim, Yeolib (Scriptura, 2005)
This article is the third and final one in a series of articles on Psalm 78. The different articles are part of an experiment in a multidimensional reading and each of them deals independently with an aspect of the interpretation of Psalm 78. While the previous two articles deal with the textual and authorial dimensions of Psalm 78,this article will deal with the dimension of the reader and will make some final concluding remarks on the whole series. The diachronic aspect of the reader, on the one hand, can be described from the first (original) hearers/readers of the text up to modern readers because reception is an ongoing process which constitutes a continuation of the diachronic aspect. On the other hand, the synchronic aspect of the reader is constituted by the context in which and from which readers operate. As stated in the first article of this series accepting the principle of a pluralism of exegetical methodologies is a methodological presupposition for this study. Based on this presupposition various exegetical methods that elucidate the meaning of the psalm have been employed in this study. As basis for this plurality of exegetical methodologies, the communication model has been adapted as hermeneutical framework. As a result, the three basic elements of the communication process (the sender, the medium, and the receiver) constitute the model of this multidimensional reading of Psalm 78. Based on the mutual relationship between diachronic and synchronic aspects, the investigation of the heading, of the tradition history, of the dating and the historical setting (with Sitz im Leben), and the study of the canonical shape of Psalm 78 have all contributed to yield some new and fresh insight for understanding the psalm’s own genesis.